Potensi Perbankan Syariah di Indonesia Dalam Pola Dasar Manajemen dan Dana Pihak Ketiga - Himyar Pasrizal; Fauza Dwi Zetria (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This article aims to examine the potential of sharia banking in Indonesia in terms of basic management patterns and third party funds. The method used in this research is the library research. The research results explain that sharia bank management is reflected in the annual financial report published by the OJK and contains the Third Party Funds of the sharia bank concerned. The potential for sharia banking in Indonesia shows a positive value, this is reflected in the total assets as of January 2023 owned by Sharia Commercial Banks and Sharia Business Units reaching IDR 765.36 trillion. This is also supported by an increase in Third Party Funds by 12% which is able to make BSI one of the largest sharia banks in Indonesia in the position of the sixth largest bank in Indonesia and the fourteenth position of the largest sharia bank in the world with Third Party Funds of 261. 49 Trillion